2005
DOI: 10.1007/s00270-004-0076-7
|View full text |Cite
|
Sign up to set email alerts
|

Primary Stenting of Intracranial Atherosclerotic Stenoses

Abstract: Prophylactic primary stenting of intracranial stenoses of the anterior or posterior cerebral circulation can be performed with a low complication rate; technical problems such as stent flexibility must still be solved. Local thrombolysis followed by stenting in stenosis-related thrombotic occlusion is technically possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…10 -12 Apart from that, effective treatment procedures have been reported for cases of subacute stent thrombosis after coronary angioplasty. [13][14][15][16] Several reports [17][18][19][20] suggest intracranial angioplasty as a technically feasible and clinically effective way to treat symptomatic intracranial arterial stenoses, which results in a substantial reduction in long-term stroke and death rates. Nevertheless, the overall number of patients being included in these studies is relatively small compared with cases presented in the interventional cardiology literature.…”
mentioning
confidence: 99%
“…10 -12 Apart from that, effective treatment procedures have been reported for cases of subacute stent thrombosis after coronary angioplasty. [13][14][15][16] Several reports [17][18][19][20] suggest intracranial angioplasty as a technically feasible and clinically effective way to treat symptomatic intracranial arterial stenoses, which results in a substantial reduction in long-term stroke and death rates. Nevertheless, the overall number of patients being included in these studies is relatively small compared with cases presented in the interventional cardiology literature.…”
mentioning
confidence: 99%
“…Reported activated clotting time target ranges during the procedure for intracranial revascularization range between 150 to 200 seconds,58 200 to 250 seconds,59 95 96 200 to 300 seconds,2 250 to 300 seconds,87 250 to 350 seconds,61 97 or 300 to 350 seconds 96. Intravenous heparinization is either stopped immediately2 59 61 or maintained for up to 24 hours58 61 83 87 or longer after the procedure, depending on the individual patient 58 83 98–100. At the end of the procedure, heparin is typically not reversed.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have been published reporting a progressive technical improvement through the use of undersized balloons and slow balloon inflation, which overcome the risk of intimal dissection, thrombosis, recoiling, and vessel rupture [8]. Most of these studies reported single-center experiences on a small series and heterogeneous results in term of periprocedural risk, ranging from 0 to 11.8% [4,[9][10][11][12][13][14][15][16][17]. Recently, a new family of self-expanding stents, adapting to target vessels shape and anatomy, was specifically designed for treatment of intracranial stenoses.…”
Section: Introductionmentioning
confidence: 99%